2022
DOI: 10.14710/ijred.2023.47761
|View full text |Cite
|
Sign up to set email alerts
|

Microgrid Hybrid Solar/Wind/Diesel and Battery Energy Storage Power Generation System: Application to Koh Samui, Southern Thailand

Abstract: This paper presents the optimization of a 10 MW solar/wind/diesel power generation system with a battery energy storage system (BESS) for one feeder of the distribution system in Koh Samui, an island in southern Thailand.  The main objectives are to maximize the deployment of renewable energy-based power generation and to minimize the levelized cost of energy (LCOE).  A hybrid renewable energy-based power generation system, consisting of solar PV, wind turbine generators, diesel generator (DiG), bi-directional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…On another hand, Regarding the validity of the HOMER model, the software has been widely used and validated by numerous studies, both numerically and experimentally. Several validation studies have demonstrated the capability of HOMER and its use in research projects, while allowing the programmer to compare various design architectures on the basis of their technical and financial merits (Chouaib et al 2017, Alsafasfeh 2015, Barakat et al 2016, Çetinbaş et al 2019, Alshammari et al 2018, Hassane et al 2022, Khamharnphol et al 2023, Diyoke et al 2023, Mahmoudi et al 2023, Ariae et al 2019). Additionally, HOMER has been validated against multiple software and techniques, as for example in the study of Milosavljević et al 2022.…”
Section: Technical and Economic Inputsmentioning
confidence: 99%
“…On another hand, Regarding the validity of the HOMER model, the software has been widely used and validated by numerous studies, both numerically and experimentally. Several validation studies have demonstrated the capability of HOMER and its use in research projects, while allowing the programmer to compare various design architectures on the basis of their technical and financial merits (Chouaib et al 2017, Alsafasfeh 2015, Barakat et al 2016, Çetinbaş et al 2019, Alshammari et al 2018, Hassane et al 2022, Khamharnphol et al 2023, Diyoke et al 2023, Mahmoudi et al 2023, Ariae et al 2019). Additionally, HOMER has been validated against multiple software and techniques, as for example in the study of Milosavljević et al 2022.…”
Section: Technical and Economic Inputsmentioning
confidence: 99%
“…The PV system converts the energy from sunlight in photons directly into electricity (Khamharnphol et al, 2023). However, the electrical power generated by the conversion significantly depends on several factors, including cell structure, cell, and ambient temperature, temperature coefficient, derating factor, solar radiation, as well as the environmental and meteorological conditions at the installation site (Çetinbaş et al, 2019) The implementation of PV systems in coastal areas has several advantages and challenges.…”
Section: Pv System Configurationmentioning
confidence: 99%
“…By giving precedence to renewable sources, microgrids can reduce reliance on non-renewable backup generators and improve sustainability. [6]proposed a renewable-energy-based microgrid control strategy that prioritizes solar and wind generation, using backup generators only when necessary. Their results demonstrated the effectiveness of the control strategy in reducing carbon emissions and improving system efficiency.…”
Section: Overview Of Microgrid Controlmentioning
confidence: 99%